2001
DOI: 10.1093/ajcn/74.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Effects on blood lipids of a blood pressure–lowering diet: the Dietary Approaches to Stop Hypertension (DASH) Trial

Abstract: The DASH diet is likely to reduce coronary heart disease risk. The possible opposing effect on coronary heart disease risk of HDL reduction needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
224
2
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(242 citation statements)
references
References 46 publications
13
224
2
3
Order By: Relevance
“…Specifically, the increase in fruit and vegetable consumption and the decrease in saturated fat, fried food, and fast food consumption at worksite A help to explain the observed improvements in blood pressure and lipid concentrations. These benefits are consistent with results of the DASH (i.e., Dietary Approaches to Stop Hypertension) diet studies (Appel et al, 1997;Sacks et al, 2001;Obarzanek et al, 2001), and are the reason that the DASH eating plan (U.S. Department of Health and Human Services, 2006) is recommended in the current Dietary Guidelines for Americans (U.S. Department of Health and Human Services and U.S. Department of Agriculture, 2005). Furthermore, our observation in the present study that moderate physical activities such as walking promoted higher fitness levels is in agreement with previous intervention studies (Duncan et al, 1991;Dunn et al, 1999;Murphy et al, 2007) and observational studies (Blair and Brodney, 1999).…”
Section: Discussionsupporting
confidence: 64%
“…Specifically, the increase in fruit and vegetable consumption and the decrease in saturated fat, fried food, and fast food consumption at worksite A help to explain the observed improvements in blood pressure and lipid concentrations. These benefits are consistent with results of the DASH (i.e., Dietary Approaches to Stop Hypertension) diet studies (Appel et al, 1997;Sacks et al, 2001;Obarzanek et al, 2001), and are the reason that the DASH eating plan (U.S. Department of Health and Human Services, 2006) is recommended in the current Dietary Guidelines for Americans (U.S. Department of Health and Human Services and U.S. Department of Agriculture, 2005). Furthermore, our observation in the present study that moderate physical activities such as walking promoted higher fitness levels is in agreement with previous intervention studies (Duncan et al, 1991;Dunn et al, 1999;Murphy et al, 2007) and observational studies (Blair and Brodney, 1999).…”
Section: Discussionsupporting
confidence: 64%
“…[14][15][16] Low-fat diets with reduced saturated fat and cholesterol levels have also been shown to reduce LDL cholesterol levels. [1][2][3]17 The present study demonstrated that a weight-reducing, 25% fat, olestracontaining diet fed for 9 months significantly reduced total and LDL cholesterol compared to a control 33% fat diet or standard 25% fat diet. Although dietary saturated fat was somewhat reduced on the FS diet compared to the control (Table 1), the predicted changes in serum lipids from changes in fatty acid composition based on standard equations were considerably less than the observed changes.…”
Section: % Body Fat Changesupporting
confidence: 54%
“…While isocaloric low-fat diets have been shown experimentally to lower total and low-density lipoprotein (LDL) cholesterol relative to high-fat diets, they also appear, at least in the short term, to lower high-density lipoprotein (HDL) cholesterol [1][2][3] and raise serum triglycerides. 1 This has caused some to argue that low-fat diets may not be the best nutritional approach for preventing heart disease, 4 although the effect of low-fat diets on lipids is clearly impacted by whether weight is maintained or decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…10 The DASH diet also improves measures of cardiovascular disease risk, including LDL cholesterol and insulin sensitivity. [11][12][13] Peripheral vascular function is an important contributor to BP. In established hypertension, the major abnormality is increased total peripheral resistance.…”
Section: Introductionmentioning
confidence: 99%